Outbreaks of Foodborne Illnesses Associated with Tomatoes - Matthew Krug; Angela Valadez; Travis Chapin; Keith Schneider; Michelle Danyluk (EDIS, 2020)
This document provides a comprehensive list of tomato-related outbreaks in the United States to serve as a reference for everyone interested in the safety of fresh-market tomatoes.